Comparative transcriptome analysis reveals new molecular pathways for cucumber genes related to sex determination - Pawełkowicz, Magdalena (Plant Reprod, 2019)
KEY MESSAGE: Transcriptome data and qPCR analysis revealed new insight into genes regulatory mechanism related to cucumber sex determination. ABSTRACT: Cucumber (Cucumis sativus L.) is an economically important crop cultivated worldwide. Enhancing the genomic resources for cucumber may enable the regulation of traits relevant to crop productivity and quality. Sequencing technologies and bioinformatics tools provide opportunities for the development of such resources. The aims of this study were to identify and characterize the genes involved in sex determination and flower morphogenesis in cucumber isogenic lines that differed regarding flower sex type. We obtained transcripts for 933 genes related to shoot apex development, among which 310 were differentially expressed genes (DEGs) among the male, female, and hermaphroditic lines. We performed gene ontology and molecular network analyses and explored the DEGs related to already known processes like: hormone synthesis and signaling, lipid and sugar metabolism; and also newly discovered processes related to cell wall, membrane, and cytoskeleton modifications; ion homeostasis which appears to be important for ethylene perception and signaling, and genes expression mediated by transcription factors related to floral organ identities. We proposed a new model of regulatory mechanism network of sex development in cucumber. Our results may be useful for clarifying the molecular genetics and the functional mechanisms underlying the sex determination processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00497-019-00362-z) contains supplementary material, which is available to authorized users.